Self Compacting Concrete – an Analysis of Properties using Fly Ash - A K, Dasarathy; Tamil Selvi, M; Leela, D; Kumar, S (International Journal of Engineering and Technology, 2018)
Self  compacting concrete has ability involves not only high deformability of paste or mortar, but also resistance to segregation between coarse aggregate and  mortar  when the concrete flows  through the confined zone of reinforcing bars. Several researchers have employed the different methods to achieve self- compactability. In recent years, self-compacting concrete (SCC) has gained wide use for placement in congested reinforced  concrete structures with difficult casting conditions. For such applications, the fresh concrete must possess high fluidity and good cohesiveness. The initial results of an experimental program aimed at producing and evaluating SCC made with high volumes of fly ash are presented and discussed. Nine SCC mixtures and one control concrete were investigated in this study. The content of the cementitious materials was maintained constant (400 kg/m3), while the water / cementitious material ratios ranged from 0.35 to 0.45. The self-compacting mixtures had a cement replacement of 40,50 and 60% by Class F fly ash. Tests were carried out on all  mechanical properties of hardened concretes such as compressive strength were also determined. The self-compacting concretes developed a 28- day compressive strengths ranging from 26 to 48 MPa. The results show that an economical self-compacting concrete could be successfully developed by incorporating high-volumes of Class F fly ash. The present project investigates the making of self-compacting concrete more affordable for the construction market by replacing high volumes of Portland cement by fly ash. The study focuses on comparison of fresh properties of SCC containing varying amounts of fly ash with that containing commercially available admixture. Test result substantiate the feasibility to develop low cost SCC using Class F fly ash.